EFECTO DE DISTINTOS TIPOS DE ENVASE, SUSTRATO y GRADOS DE ENDURECIMIENTO EN LA PRODUCCIÓN DE PLANTA DE QUERCUS SUBER L. y QUERCUS ROTUNDIFOLIA LAM. (II Congreso Forestal Español, 1997)
Different treatments about olm oak (Quercus rotundifolia Lam.) and cork oak (Quercus suber L.) plants' production are comparied. It has been worked with two kinds of containers, three kinds of substratums and two degrees of plants' protection during the cultivation

EFECTOS DE DISTINTOS TRATAMIENTOS EN VIVERO EN EL ARRAIGO Y PRIMER DESARROLLO EN CAMPO DE PLANTAS DE QUERCUS SUBER L. y QUERCUS ROTUNDIFOLIA LAM .. EFECTO DEL PROTECTOR. (II Congreso Forestal Español, 1997)
The rootting ability and the first developes of cork oak and olm oak seedlings cultivated on different substratums and containers, as well as different harding degrees are comparied. The individual protector's effect is also analyzed.